Comparative study of intradiurnal variations of airborne pollen in the city centre and on the outskirts of Malaga city (southern Spain) - Ruiz-Mata, Rocío; Picornell Rodríguez, Antonio; De Gálvez-Montañez, Enrique; Recio-Criado, María Marta; Trigo-Pérez, María del Mar (My University, 2022)
Airborne pollen is one of the main causative agents of allergic rhinitis in cities all over the world. Pollen concentrations may vary throughout the day, not being equal in all the points of the city, due to these concentrations are influenced by the presence of nearby pollen emission sources. Knowledge about the influence of these sources is of great interest to allergy sufferers when planning outdoor activities. The aim of this study was to analyse the intradiurnal variation patterns of the airborne pollen concentration both in the city centre and on the outskirts of Malaga as well as quantify the detected differences and establish the influence of the pollen emission sources present in the nearby areas. The aerobiological data were obtained by means of two Hirst-type volumetric pollen traps. One of them was installed on the rooftop of the Faculty of Sciences, University of Malaga (outskirts) and the other in the city centre. The study was carried out during the years 2017-2019, with the most relevant pollen types being considered. Despite the two sampling points being only 5 km apart, notable variations were detected in the intradiurnal patterns of some pollen types because of the location of the nearby pollen emission sources. This reflects the need to conduct aerobiological sampling in several points of the same city in order to obtain more precise and useful information for the allergic population.
Keywords: Polen; Alergia; Aerobiología; Alergias respiratorias